The effect of physicians’ communication skills on patients’ satisfaction - Mahsa Narenjiha; Shahpar Haghighat; Hamdollah Baahador; Jila Shajari; Fatemeh Haji Molla Hoseini (مجله ایرانی آموزش در علوم پزشکی, 2012)
Introduction: A pleasing communication and interaction between physician and patient can be effective in patients’ satisfaction, treatment outcome, medical charges, clinical services quality, and even claim against physicians. This study was performed to evaluate patients’ satisfaction with physicians’ manners with them in Ghods Clinic of Tehran in year 2010. Methods: Totally 392 patients were asked in this descriptive cross-sectional study. Satisfaction among patients referred to Ghods Clinic of Tehran in year 2010 was measured considering several aspects whereas physicians’ behavior, physical examination and interview, communication and education to the patient, follow-up, responsibility to questions, and giving information. These data was gathered using Patient Satisfaction Questionnaire and the effect of variables such as gender, marital status, job, and academic level on satisfaction score was investigated. Data was analyzed using statistical tests of t, ANOVA, and Pearson correlation coefficient. Results: The results of the study showed that the highest satisfaction scores were obtained from education skills of physicians (mean: 55.8±24.1) and responsibility to questions (mean: 49.2 ±6.58) and the lowest was physical examination skills (mean: 31.25 ± 22.76). Satisfaction mean score among patients enjoying a higher level of education (p = 0.002) and patients who were employee (p = 0.006) compared to business people was higher and showed significant difference. Conclusion: It seems that the physicians should try more to satisfy people with lower educational levels and different social positions by spending more time and employing appropriate communication skills. Education and emphasis on improvement of these skills leads to promotion in health services.